Stress and mental health - Spence, Annette. 4 0 16; 5 (New York : Facts on File Publications, 1988)
Part of a six-volume series of books on health topics significant to junior-high students. Explains stress and how to control it.
A Friedman Group book--T.p. verso.;Includes index.
6.7;5-8;5-8
Keywords: 2 -- 0; 6; Stress (Psychology);Mental health.;Stress (Psychology);Mental health; 20; 2